Integralna ochrona środowiska w nauczaniu Jana Pawła II - Wojciech Bołoz (Studia Ecologiae et Bioethicae)
In his teaching John Paul II paid a lot of attention to the subject of environmental protection. His holistic concept incorporates the most important issues that relate to preservation of natural resources that still exist. Among many issues discussed by him the following seem to be of the highest importance.